2017
DOI: 10.1128/msystems.00047-17
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Depletes Acidogenic Taxa in Oral but Not Gut Microbial Communities in Mice

Abstract: Fluoride has been added to drinking water and dental products since the 1950s. The beneficial effects of fluoride on oral health are due to its ability to inhibit the growth of bacteria that cause dental caries. Despite widespread human consumption of fluoride, there have been only two studies of humans that considered the effect of fluoride on human-associated microbial communities, which are increasingly understood to play important roles in health and disease. Notably, neither of these studies included a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…These fluoride-induced microbial changes were associated with histological gut abnormalities including evidence of a damaged epithelial barrier, decreased crypt depth, and lower epithelial cell proliferation, relative densities of goblet cells, glycoproteins, and intestinal mast cells (Liu et al 2019b). However, one study in mice found no significant shifts in gut microbial community composition with a lower dose and shorter duration of fluoride added to water (Yasuda et al 2017). Therefore, fluoride can alter the intestinal microbiota and gut health in ways that may influence blood glucose, but the dose and duration of fluoride are key factors to consider.…”
Section: Fluoridementioning
confidence: 99%
“…These fluoride-induced microbial changes were associated with histological gut abnormalities including evidence of a damaged epithelial barrier, decreased crypt depth, and lower epithelial cell proliferation, relative densities of goblet cells, glycoproteins, and intestinal mast cells (Liu et al 2019b). However, one study in mice found no significant shifts in gut microbial community composition with a lower dose and shorter duration of fluoride added to water (Yasuda et al 2017). Therefore, fluoride can alter the intestinal microbiota and gut health in ways that may influence blood glucose, but the dose and duration of fluoride are key factors to consider.…”
Section: Fluoridementioning
confidence: 99%
“…Similarly, exposure to fluoride can induce the imbalance of microbiological composition. Yasuda et al (2017) found that fluoride exposure causes a depletion of acidogenic bacterial genera in oral community. Luo et al (2016) reported that excessive fluoride intake induces a reduction of Lactobacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, uoride failed to promote the proliferation of Erysipelotrichaceae in the absence of HFD, which might explain why uoride could not induce obesity in ND mice. In a similar work, uoride also showed limited effect on gut microbial communities in mice fed on standard mouse chow [57].…”
Section: Discussionmentioning
confidence: 73%